Prevalence and determinants of overweight and obesity among higher secondary students in a district in Kerala - George, Babu; Raju, Juby R. A.; Leela, Leena M.; Bhaskaran, Deepa; Indiradevi, Lalikumari; Thulaseedharan, Neethu; Mahendran, Preema; Scaria, Liss M. (International Journal Of Community Medicine And Public Health, 2021)
Background: Overweight and obesity among adolescents and children are associated with early onset of non-communicable diseases and greater risk of complications in adulthood. The study was conceived in the background of the high burden on adult non-communicable diseases in the state, to assess the prevalence and determinants of overweight and obesity among higher secondary students in one of its fourteen districts, with a view to explore the areas to be focused in preventive activities. Methods: Anthropometric, blood pressure, and physical examination of 1846 class plus one students were conducted in Thiruvananthapuram. Lifestyle assessment of the children was also conducted using a self-administered prevalidated questionnaire. Prevalence of overweight and obesity was calculated based on Indian academy of pediatrics body mass index cut-offs. Logistic regression analysis was done to discover factors associated with overweight conditions. Results: Among the students, 14.19% were overweight; 6.45% were obese. Boys, rural residents, and those from low socioeconomic background had lower odds of being overweight. Students who had main meal (s) from outside on three or more days a week (adjusted odds ratio 1.99; CI: 1.17-3.386), and with history of hypercholesterolemia (adjusted odds ratios (aOR) 1.8; CI: 1.19-2.63), obesity (aOR 1.6; CI: 1.11-2.23), or diabetes (aOR 1.5; CI: 1.17-1.95) in the immediate-family had higher odds of being overweight. Hypertension and acanthosis were significantly higher among overweight students (p=0.001). Conclusions: The results warrant the adoption of screening and timely intervention for non-communicable disease risk factors from school level itself to reduce future morbidity and the risk of complications.